2011
DOI: 10.1088/0953-8984/23/39/394204
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated magnetization reversal in monatomic magnetic chains on surfaces studied by classical atomistic spin-dynamics simulations

Abstract: We analyze the spontaneous magnetization reversal of supported monoatomic chains of finite length due to thermal fluctuations via atomistic spin-dynamics simulations. Our approach is based on the integration of the Landau-Lifshitz equation of motion of a classical spin Hamiltonian at the presence of stochastic forces. The associated magnetization lifetime is found to obey an Arrhenius law with an activation barrier equal to the domain wall energy in the chain. For chains longer than one domain-wall width, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Refs. [48][49][50]). However, one has to keep in mind that Stoner excitation will impact on the position of spin waves resonances via the real part of the Kohn-Sham susceptibility, which will be the topic of the next paragraph.…”
Section: A Imaginary Part Of the Slope Of χ0mentioning
confidence: 99%
“…Refs. [48][49][50]). However, one has to keep in mind that Stoner excitation will impact on the position of spin waves resonances via the real part of the Kohn-Sham susceptibility, which will be the topic of the next paragraph.…”
Section: A Imaginary Part Of the Slope Of χ0mentioning
confidence: 99%
“…Because of varying environments, there is no unique set of ab initio exchange functions in cobalt. 39 So J is determined by fitting various first-principles calculations on the exchange energy of cobalt in fcc, hcp, and one-dimensional structures. [40][41][42] Figure 2 shows that first-principles exchange functions are very small from the second neighbors as expected.…”
Section: B Determination Of Parametersmentioning
confidence: 99%
“…Because both situations consider cobalt-based nanostructures, one has to pay attention to the strength of the interaction potential with respect to its bulk parametrization. In particular, it is known that the magnetic interaction is reinforced in low dimensions 39 and the exchange interaction parameter given in Fig. 2 has to be slightly rescaled.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of temperature and magnetic anisotropy have been the subject of previous theoretical studies of spin dynamics in spin chains16171819 where the relaxation dynamics was found to depend substantially on the description of the magnetic anisotropy. Recently, analytical solutions were obtained for the dynamics of intrinsic localized modes, in particular in form of one-spin, two-spin and three-spin excitations, of an anisotropic Heisenberg ferromagnetic spin chain in the presence of an external magnetic field20.…”
mentioning
confidence: 99%